Examining the Influence of Academic Nurse Educator Doctoral Degree Preparation on National League for Nursing Core Competency Skill Acquisition. Issue 5 (September 2021) - Sebach, Aaron M.
Abstract: AIM: The purpose of the study was to examine the influence of academic nurse educator doctoral degree preparation on National League for Nursing (NLN) core competency skill acquisition. BACKGROUND: Doctor of nursing practice (DNP) and doctor of philosophy (PhD) graduates frequently seek faculty positions, yet neither degree exclusively prepares graduates for careers in academia. METHOD: A descriptive, correlational design was utilized to examine the influence of doctoral degree preparation on NLN core competency skill acquisition. A randomized, nationwide sample ( N = 160) of full-time nurse educators teaching in American Association of Colleges of Nursing member schools across the United States completed the Nurse Educator Skill Acquisition Assessment. RESULTS: PhD-prepared educators reported higher NLN core competency skill acquisition scores than DNP-prepared nurse educators. There were statistically significant differences in overall skill acquisition scores between DNP- and PhD-prepared nurse educators and for the "use assessment and evaluation" and "engage in scholarship" domains. CONCLUSION: These findings provide opportunities for NLN core competency skill acquisition among DNP- and PhD-prepared faculty. Abstract : Supplemental digital content is available in the text.